Identification of Pancreatic Cancer-Associated Tumor Antigen from HSP-Enriched Tumor Lysate-Pulsed Human Dendritic Cells - Kim, Han-Soo; Kang, Dukjin; Moon, Myeong Hee; Kim, Hyung Jik (Yonsei medical journal, 2014)
Vaccine strategies utilizing dendritic cells (DCs) to elicit anti-tumor immunity are the subject of intense research. Although we have shown that DCs pulsed with heat-treated tumor lysate (HTL) induced more potent anti-tumor immunity than DCs pulsed with conventional tumor lysate (TL), the underlying molecular mechanism is unclear. In order to explore the molecular basis of this approach and to identify potential antigenic peptides from pancreatic cancer, we analyzed and compared the major histocompatibility complex (MHC) ligands derived from TL- and HTL-pulsed dendritic cells by mass spectrophotometry. Human monocyte-derived dendritic cells were pulsed with TL or HTL prior to maturation induction. To delineate differences of MHC-bound peptide repertoire eluted from DCs pulsed with TL or HTL, nanoflow liquid chromatography-electrospray ionization-tandem mass spectrometry (nLC-ESI-MS-MS) was employed. HTL, but not TL, significantly induced DC function, assessed by phenotypic maturation, allostimulation capacity and IFN-γ secretion by stimulated allogeneic T cells. DCs pulsed with TL or HTL displayed pancreas or pancreatic cancer-related peptides in context of MHC class I and II molecules. Some of the identified peptides had not been previously reported as expressed in pancreatic cancer or cancer of other tissue types. Our partial lists of MHC-associated peptides revealed the differences between peptide profiles eluted from HTL-and TL-loaded DCs, implying that induced heat shock proteins in HTL chaperone tumor-derived peptides enhanced their delivery to DCs and promoted cross-presentation by DC. These findings may aid in identifying novel tumor antigens or biomarkers and in designing future vaccination strategies.